ANALISIS PENGARUH KESELAMATAN KERJA DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan PT. Java Prima Abadi Semarang ) - Styawati, Aprilia Nining; Soedarmadi, Soedarmadi (Fakultas Ekonomi, Universitas Semarang, 2021)
Abstract This study aims to determine the influence of 1). Work safety on job satisfaction, 2). Occupational health towards job satisfaction, 3), job satisfaction on employee performance, 4) work safety on employee performance, and occupational health on employee performance. as well as the indirect effect of job satisfaction. Between work safety, occupational health on employee performance at PT. Java Prima Abadi Semarang The data collection technique was done by filling out a questionnaire by a sample of 74 employees taken from a population of 106 employees. Furthermore, answers through closed questions by choosing one of the appropriate answers according to the respondent on a rating scale of one (strongly disagree), two (disagree), three (neutral), four (agree), and five (strongly agree). Then tabulated into the exel program. CSV, to be processed into Smart PLS version 3 .. The results prove that there is a direct effect of occupational safety, occupational health, and positive significant job satisfaction on employee performance, and there is an indirect effect of occupational safety and health through significant positive job satisfaction on employee performance, but it has no impact on employee performance because the effect value is smaller than the direct effect. Keywords: Occupational Safety, Occupational Health, Job Satisfaction, Employee Performance.